Effect of Angelica polysaccharide on brain senescence of Nestin-GFP mice induced by D-galactose. (January 2019) - Cheng, Xiao; Yao, Hui; Xiang, Yue; Chen, Linbo; Xiao, Minghe; Wang, Ziling; Xiao, Hanxianzhi; Wang, Lu; Wang, Shunhe; Wang, Yaping
Abstract: The incidence of neurodegenerative diseases is severely increasing with the aging. It has been proposed that NSCs (neural stem cells) help to control aging, but the mechanisms responsible remain unclear. Angelica polysaccharide is an active ingredient of Angelica sinensis in traditional Chinese medicine, which possesses versatile pharmacological activities including anti-oxidative and anti-aging effects. In this study, D-gal (D-galactose) was used to construct an aging model of Nestin-GFP transgenic mice brain tissues and NSCs. Mouse model was subcutaneously injected with D-gal, as we observed that mice consistently displayed acceleration of aging-like behavior change, energy metabolism decreased, the expression of aging-related genes was up-regulated. Conversely, aging retardation was achieved in Nestin-GFP mice Induced by D-gal that was locally injected with ASP (Angelica polysaccharide). Mechanistically, we isolated and cultured NSCs in vitro. ASP protected NSCs by increasing the cell proliferation; decreasing the number of SA-β-gal stained neurons; increasing the activity of SOD(superoxide dismutase) and T-AOC(total antioxidant capacity), decreasing the content of MDA(malondialdehyde); decreasing the levels of IL-1b, IL-6, TNF-a and ROS; and down-regulated the expression of cellular senescence associated genes p53, p21 in the aging NSCs. In conclusion, ASP can delay aging speed by protecting NSCs and promote neurogenesis by enhancing the antioxidant and anti-inflammatory capacity, up-regulation of p53/p21 signaling pathway. As to provide theoretical basis for treatment for brain aging related diseases, add new scientific connotation for "qi and blood theory" and "supplement blood and delay aging" of Traditional Chinese Medicine. Highlights: By constructing the model of mice brain aging, we studied the mechanism of ASP retarding brain aging and aging of NSCs. The topic explains the connotation of "supplement blood and delay aging" of Traditional Chinese Medicine. Mechanisms that regulate NSCs aging provide an important basis for the treatment of brain aging related diseases.